Permanence and changes in pastoral farming in the Southern Alps - Laurent Garde; Marc Dimanche; Jacques Lasseur (Revue de Géographie Alpine)
The Southern Alps, where sheep farming is highly prevalent, is specific to the mountains of the Mediterranean region and, consequently, is in sharp contrast with the Northern Alps. The age-old practice of pastoralism that has shaped the landscapes and human societies has existed for thousands of years, questioning the emergence of the concept of naturality linked to this region. Nevertheless, the perception of the durability of an activity seen as traditional should not obscure the extent of changes that have had an impact on it in the past. In light of this, there is much to learn from the comparison between the major upheaval that affected pastoral farming at the end of the 19th century, and the current process of change whose outcome is not yet known. In both cases, changes in public policies and markets, as well as the emergence of new environmental stakes have determined or are in the processes of determining the future of pastoral farming. Faced with society’s increasingly specific but sometimes contradictory expectations, the types of livestock farming widely used in pastoral areas thus appear to be the best adapted to propose "natural" and local products, but the most vulnerable as well in view of the establishment of a large population of wolves. This contradiction is indicative of the shock of values between two societal projects for abandoned land, the first, heir to a rural tradition that is responsible for maintaining a human presence in the mountains, and the second, the vector of a “naturality” based on the reconstitution of ecological pyramids.